IFRS accounting systems’ classification: a new emerging cluster - Sarquis, R.; Luccas, R.; Lourenço, I.; Dalmácio, F. (37th Annual Congress of the European Accounting Association EAA, 2014)
This study aims to identify the position of emerging countries in the IFRS accounting systems’ classification proposed by Nobes (2011). In spite of the international accounting harmonization efforts around the convergence to IFRS, there is empirical evidence of significant differences in the way IFRS has been applied worldwide. The traditional split between Anglo and Continental European countries are still observed even in an IFRS environment (Nobes, 2011). Considering the weight of emerging countries in the global economy, this research analyzes the accounting practices in the three BRICS countries that have adopted IFRS (Brazil, Russia and South Africa) in order to identify how they stand in the classification of accounting systems proposed by Nobes (2011). Our findings provide empirical evidence that there is a new cluster composed by the emerging countries, which is closer to the Continental European group than to the Anglo group. Curiously, the Netherlands, considered as an unclassifiable country, became closer to South Africa and then fused with the Emerging country cluster. The other countries are still in the same position shown by Nobes (2011), in the Anglo or in the Continental European group.